THE PHENOMENON OF CYCLING TRENDS DURING THE COVID 19 PANDEMIC IN SURAKARTA - Herman Wibisono, Gideon; Santosa, Teguh; Hutomono, Shodiq (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2021)
The aim of this study was to find out: (1) public interest in maintaining physical fitness by cycling in Surakarta during the Covid 19 pandemic, (2) community motivation in maintaining physical fitness by cycling in Surakarta during the Covid 19 pandemic, and (3) the right way to cycle and a suitable cycling program for beginners, according to the cycling community. This research was a qualitative research method which was based on post positivism philosophy, where truth is in accordance with the nature of the object, used to examine the condition of the natural object, where the researcher is the key instrument, and the research results emphasize meaning rather than generalization (Sugiyono, 2007: 15). The data was collected from 50 people who cycled in Surakarta during the pandemic. The data analysis used in this study was the Analysis Interactive Model from Miles and Huberman, which divided the steps into several parts, namely data collection, data reduction, and data reduction, data display, and drawing conclusions or verification (conclusions).According to the findings of a survey of 50 visitors, the intrinsic motivation is the motivation for cycling in the Surakarta community during the Covid 19 pandemic. Cycling motivation is dominated by physiological needs to maintain fitness. Extrinsic motivation for cycling in the Surakarta community is dominated by a desire to stay fit and participate in enjoyable and simple sports. Meanwhile, there are other interests such as attracting attention, business relations/relationships, a way to gather and vacation with family, equipment that is easy to obtain or rent, reasons to join the Solo bicycle community, and a way to unwind, get bored, and fill spare time. The benefits of cycling activities during the COVID-19 pandemic are influenced by the benefits of exercising to maintain fitness during the COVID-19 pandemic.